Pengaruh Green Reward terhadap Produktivitas Kerja dengan Motivasi Kerja sebagai Variabel Mediasi pada Karyawan UMKM Pabrik Kerupuk Kulit - Muhammad Natan Yafi Daffa Haq; Renny Rochani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The implementation of environmentally friendly operational practices in Micro, Small, and Medium Enterprises (MSMEs) faces challenges in balancing production efficiency with sustainable environmental management. This study aims to analyze the effect of green rewards on employee work productivity, with work motivation serving as a mediating variable, at an MSME leather cracker factory. This explanatory quantitative study employed a survey of 80 employees selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (PLS-SEM) with SmartPLS 4. The results indicate that green rewards have a positive and significant effect on work motivation (Coefficient = 0.486; P = 0.000), while work motivation has a positive and significant effect on work productivity (Coefficient = 0.655; P = 0.000). However, green rewards have no significant direct effect on work productivity (Coefficient = −0.020; P = 0.814). Work motivation was found to fully mediate the relationship between green rewards and work productivity, with an indirect effect coefficient of 0.318 (P = 0.000).